Prevotella as the main driver for the association between dairy farming and human gut microbiome composition - Cuperus, Tryntsje; Kool, Jolanda; Boverhoff, David; van der Ark, Kees; Opsteegh, Marieke; Fuentes, Susana (Frontiers in Microbiomes, 2025)
The human gut microbiota is shaped by a multitude of environmental factors, including contact with animals. To investigate the association between occupational exposure to cattle and the gut microbiome, a cross-sectional study was performed on 65 individuals working and/or living on Dutch dairy cattle farms in comparison to controls. The gut microbiome of the participants was assessed by 16S rRNA gene amplicon sequencing of stool samples. A lower alpha diversity and divergent microbiome composition was observed, driven largely by a greater Prevotella abundance in dairy farm participants when compared to controls. Prevotella was also associated with contact frequency with the dairy cattle, with participants with more frequent contact showing higher abundance. The results of this study show occupational contact with cattle is associated with gut microbiome composition, which is of relevance because of the importance of the microbiome for human health.